The adventures of the Princess and Mr. Whiffle : the thing beneath the bed - Rothfuss, Patrick, 1973- (Subterranean Books, 2010)
The author describes this book as a "book for adults with a dark sense of humor and an appreciation of old-school faerie tales." There are three separate endings to the book : a sweet ending, a horrible one and the true ending.